Broad Antibody Mediated Cross-Neutralization and Preclinical Immunogenicity of New Codon-Optimized HIV-1 Clade CRF02_AG and G Primary Isolates - Agwale, Simon M.; Forbi, Joseph C.; Notka, Frank; Wrin, Terri; Wild, Jens; Wagner, Ralf; Wolf, Hans (PloS one, 2011)
Creation of an effective vaccine for HIV has been an elusive goal of the scientific community for almost 30 years. Neutralizing antibodies are assumed to be pivotal to the success of a prophylactic vaccine but previous attempts to make an immunogen capable of generating neutralizing antibodies to primary "street strain" isolates have resulted in responses of very limited breadth and potency. The objective of the study was to determine the breadth and strength of neutralizing antibodies against autologous and heterologous primary isolates in a cohort of HIV-1 infected Nigerians and to characterize envelopes from subjects with particularly broad or strong immune responses for possible use as vaccine candidates in regions predominated by HIV-1 CRF02_AG and G subtypes. Envelope vectors from a panel of primary Nigerian isolates were constructed and tested with plasma/sera from the same cohort using the PhenoSense HIV neutralizing antibody assay (Monogram Biosciences Inc, USA) to assess the breadth and potency of neutralizing antibodies. The immediate goal of this study was realized by the recognition of three broadly cross-neutralizing sera: (NG2-clade CRF02_AG, NG3-clade CRF02_AG and NG9- clade G). Based on these findings, envelope gp140 sequences from NG2 and NG9, complemented with a gag sequence (Clade G) and consensus tat (CRF02_AG and G) antigens have been codon-optimized, synthesized, cloned and evaluated in BALB/c mice. The intramuscular administration of these plasmid DNA constructs, followed by two booster DNA immunizations, induced substantial specific humoral response against all constructs and strong cellular responses against the gag and tat constructs. These preclinical findings provide a framework for the design of candidate vaccine for use in regions where the HIV-1 epidemic is driven by clades CRF02_AG and G.